Virtual development of H2 gas compressor and H2 storage system for HPDI engines. Compressed H2 storage systems towards environmentally-friendly and efficient heavy-duty vehicle engines development - Kakkos, Ioannis (My University, 2023)
Transition to alternative fuel sources constitutes a necessity for most large-scale operating industries. Although fuel-cell electric vehicles have undergone extensive research, there is an area in hydrogen potential that is yet to be thoroughly investigated. Companies are investigating hydrogen use in internal combustion engines, employing configurations such as diffusion combustion of a hydrogen spray, among others, as an alternative to diesel fuel with the scope of incorporating this technology in their heavy-duty truck fleet. This thesis performed under Volvo Group AB deals with the concept of HPDI H2 engines, mainly focusing on the storage tanks and their discharge, as well as the compressor. Simulations were performed on Matlab’s Simulink, where a model was built and incorporated with Volvo’s in-house simulation platform. Real gas assumption was implemented for hydrogen because of very high storage pressures of up to 700 bar. On these pressure levels the contribution of compressibility in the real-gas equation becomes very important. During tank discharge, it is important to simulate adiabatic and isothermal discharging since it makes a great difference on the range achieved by the vehicle. Another important parameter is payload which directly affects fuel consumption and reduces driving range. Apart from reducing the driving range, it was found that payload significantly increases the compressor power consumption.
Keywords: HPDI; CI; non-premixed; diffusion combustion; heavy-duty truck; tank discharge; tank deployment